Spectrophotometric and fluorimetric quantitation of quality-related protein fractions of wheat flour. (March 2015) - Thanhaeuser, Silvia Maria; Wieser, Herbert; Koehler, Peter
Abstract: Spectrophotometric and fluorimetric methods for quantitating quality-related parameters of wheat flour such as the gliadin (GLIA), glutenin (GLUT), and glutenin macropolymer (GMP) contents were adapted. The bicinchoninic acid (BCA) assay, the Bradford assay, the fluorescamine assay, the Naphthol Blue Black (NBB) assay, and the acid orange 12 assay were studied. Calibration functions were generated by using protein references isolated from a mixture of flours of 10 wheat cultivars. Among the assays studied, only the Bradford, the fluorescamine and the NBB assays provided useful results. The Bradford assay succeeded in quantitating the GLIA and GLUT fractions, but it was unsuitable for the GMP fraction because of the presence of SDS. All relevant protein fractions could be quantitated with the fluorescamine and the NBB assays. While the former showed higher coefficients of variation, the NBB assay was more reliable. NBB and HPLC data as well as NBB and micro-scale baking test data were strongly correlated. The NBB assay is a good alternative to chromatographic methods, which require time and sophisticated equipment. It can be adapted as easy-to-use, high throughput method that enables screening of a large number of flour samples for quality parameters in a short time per sample. Highlights: Quality-related protein fractions of wheat flour can easily be determined. Methods are fast and can be adapted for high-throughput screening. Methods can easily be carried out in a milling laboratory. The Naphthol Blue Black assay is the best alternative to chromatographic assays.